Diagnosis of injuries of the aorta and brachiocephalic arteries caused by blunt chest trauma: CT vs aortography - Fisher, RG; Chasen, MH; Lamki, N (American journal of roentgenology (1976), 1994)
The purpose of this study was to evaluate the role of chest CT in the triage of patients with potential injuries of the aorta and brachiocephalic arteries caused by blunt trauma and to test the value of chest CT scans in limiting the number of screening aortograms. A prospective study was done with 107 patients who were examined because of possible laceration of the aorta or brachiocephalic vessels. Chest radiographs were obtained in 107 patients, aortograms in 105, and chest CT scans in 90. This evaluation concentrates on the 88 patients who had both CT and aortography. Findings on CT scans were categorized as normal, equivocal, suggestive of, subtly positive for, or grossly positive for mediastinal hematoma. Findings on CT scans were considered normal in 18 patients. Sixteen had normal aortographic findings. Two of the 18 had clinical follow-up without aortography. Findings on CT scans were considered equivocal in 25 patients, suggestive of hematoma in 13, subtly positive for hematoma in 24, and grossly positive for hematoma in 10. Subsequent aortography showed injuries in four patients who had abnormal CT findings. Nineteen other patients had aortography because of grossly abnormal findings on chest radiographs, and one aortic injury was detected. The value of chest CT as a preliminary procedure to avoid thoracic aortography in patients with blunt trauma was limited in our series. Chest CT scans with normal findings effectively exclude aortic/brachiocephalic injury; however, only about 25% of our patients had chest CT scans with unequivocally normal findings, and most patients required further evaluation with aortography.